An investigation of a hemophilia A female with heterozygous intron 22 inversion and skewed X chromosome inactivation - Tan, Xiaoyan; Yang, Yi; Wu, Xia; Zhu, Jing; Wang, Teng; Jiang, Huihui; Chen, Shu; Lou, Shifeng (Frontiers in Genetics, 2025)
ObjectivesHemophilia A (HA) is an X-linked recessive inherited bleeding disorder that typically affects men. Women are usually asymptomatic carriers, and rarely presenting with severe or moderately severe phenotype. This study aims to describe a case of a 17-year-old girl with moderate HA, investigating the mechanisms of her condition and the genetic basis within her family.MethodsWe conducted coagulation tests and bleeding assessments to evaluate her bleeding phenotype. Molecular genetic examinations, karyotype analysis, X-chromosome inactivation testing, and targeted bioinformatic analysis were used to identify potential genetic etiologies.ResultsThe proband exhibited a severe bleeding phenotype and was found to be a heterozygous carrier of an intron 22 inversion (Inv22) with a normal chromosomal karyotype. No other hemostatic defects were identified through whole exome sequencing. The proband’s mother and monozygotic twin sister are also Inv22 carriers, yet remain asymptomatic with normal FVIII activity. X-chromosome inactivation experiments revealed unbalanced inactivation in the proband, leading to the silencing of the healthy X copy. Notably, several novel X-linked gene mutations (SHROOM2, RPGR, VCX3B, GAGE, GCNA, ZNF280C, CT45A, and XK) were identified in the proband compared to her monozygotic twin sister, though their impact on X-chromosome inactivation remains unclear.ConclusionOur findings suggest that the proband’s bleeding phenotype results from unbalanced X-chromosome inactivation. This research marks the first analysis of X chromosome-related gene mutations among monozygotic twins who are carriers of hemophilia A, laying the groundwork for further investigations into the disorder’s pathogenesis in women and highlighting the complexities in genetic counseling.